KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV SDN 1 RINGINPITU TULUNGAGUNG - Ufy Khayyun Umayda; Frita Devi Asriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The importance of critical thinking in the acquisition of mathematics motivates this study, especially in solving story problems that require understanding of concepts and applying logical and systematic solution strategies. Based on preliminary observations in class IV SDN 1 Ringinpitu Tulungagung, it was found that students still have difficulty in understanding, analyzing, and solving mathematical story problems. This research aims to expose the critical thinking skills of fourth-year SDN 1 Ringinpitu Tulungagung students when faced with mathematical problems. This study employs a qualitative method, using a specific type of case study and a phenomenological perspective. Purposive sampling was used to select 9 of the 28 students as subjects. Data collection methods included written examinations in the form of narrative cases, surveys and interviews with class teachers. The instrument was prepared based on four indicators of critical thinking according to Jacob & Sam, namely: clarification, assessment, inference, and strategies. The results showed that students' critical thinking skills varied, with a small proportion in the high category, but the majority were in the medium and low categories. Difficulties experienced include the inability to sort out information, formulate solution steps, and draw appropriate conclusions. The questionnaire and interview results support these findings, showing that low numeracy literacy also affects students' critical thinking skills. This research concludes that the critical thinking skills of fourth-grade students at SDN 1 Ringinpitu still require improvement, especially in terms of problem understanding and solving strategies. This study should provide assessment resources for teachers in developing courses that foster the development of critical thinking skills in students.